Cassola e il comunismo: la storia di Baba - Rossi Sebastiano, Michela (L’ospite ingrato, 2025)
The essay examines Cassola’s fiction on the Italian Resistenza, focusing on the short story Baba (1946), the novel Fausto e Anna (1952), and the short novel I vecchi compagni (1953). In these works, Cassola constructs a narrative opposition between the bourgeois intellectual (Fausto) and the communist worker (Baba). Within a narrative space that reconfigures relational dynamics by centering the communist character, the author portrays the failure of intellectual leadership. The essay further explores how this opposition shapes narrative construction – affecting plot structure, character development, and the role of the narrator – as well as its influence on defining Cassola’s distinctive form of populism.